ADMINISTRATIVE LAW PERSPECTIVE ON THE PROTECTION OF PALM OIL PLANTATION YIELDS FROM CRIMINAL ACTS - Loso Judijanto; Al-Amin (ADMIN: Jurnal Administrasi Negara, 2025)
Protecting palm oil yields from criminal acts is an important issue in the plantation industry, especially in areas with high crime rates. From an administrative law perspective, comprehensive regulations are needed to ensure security for business actors, farmers, and the surrounding community. This study focuses on analysing the legal framework, inter-agency cooperation, and the role of education as measures to prevent and address criminal activities that harm plantation yields. Through strengthened regulations, integrated monitoring, and active community involvement, it is hoped that solutions will be developed that are not only effective but also sustainable in maintaining the security and sustainability of this industry.